Analisis Yuridis Penerapan Pasal 335 Ayat (1) KUHP Pada Kekerasan Yang Dilakukan Suami Terhadap Istri (Studi Putusan No.764/Pid.Sus/2020/PN.Jkt Sel) - Hasry Nurain, Ayu; Susanti, Rahtami (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
This study aims to determine and analyze the case of Vicky Prasetyo and Angel Lelga where both of them are still married, the District Court Judge through Decision No.764/Pid.Sus/2020/PN.Jkt Sel sentenced Vicky Prasetyo using the Criminal Code. This type of research uses normative juridical legal research, with sources of legal material in the form of laws and regulations, court decisions / decrees. The types and sources of data in the research consist of three types, premier data, secondary data, and premier data. The data collection technique is to use legal research. The results of this study explain that the legal construction in the application of Article 335 Paragraph (1) committed by a husband against his wife, namely the case of Vicky Prasetyo with Angel Lelga, the court determined the decision using Pid.Sus even though the judge imposed a sentence using the Criminal Code, besides that Angel Lelga reported Vicky Prasetyo with a defamation case. Based on Decision No.764/Pid.Sus/2020/PN.Jkt Sel there is a psychological violence in the case of Vicky Prasetyo and Angel Lelga including, Angel Lelga became afraid and lost the ability to act due to the words that had been issued by Vicky Prasetyo. In addition to the psychological violence, there was also other violence, including the destruction of the bedroom door by Vicky Prasetyo.